Cluster and building block structure of amylopectin from waxy maize starch. Issue 3 (29th January 2021) - Wang, Yajuan; Qian, Jin; Liu, Di; Sun, Mengwen; Chen, Hui; Kong, Xiangli; Qiu, Dan
Abstract: Background and objectives: The aim of this study was to determine the fine structure of amylopectin of waxy maize starch, which has been widely used in industry for producing modified starch, such as the esterification with octenyl succinic anhydride. Findings: Waxy maize starch was hydrolyzed with α‐amylase for 3.5 hr to obtain structural clusters. The clusters were further treated with phosphorylase α and β‐amylase in order to remove all the outer chains. The internal structure of waxy maize starch was determined by high‐performance anion exchange chromatography with pulsed amperometric detector (HPAEC–PAD). Results showed that one single cluster contained ~ 10.9 chains, on average, and the density of branching was 15.7. The ϕ, β‐limit dextrin of clusters from waxy maize starch were treated with a concentrated solution of α‐amylase to produce small and tightly branched units, and six different structural groups were defined. The average DP of branched building blocks was 10.9, and the number of chains for building block units was 2.8. Significance and novelty: The fine structure of waxy maize starch, including the structural characteristic of cluster and building block, will provide some basic structural information for the reason why the functional properties of the starch derivatives achieved by the specific starch is superior to others.